Analisis Kinerja Anggaran Pendapatan dan Belanja Daerah Kota Tegal Sebagai Indikator Layanan Publik - Faqihudin, M. (PERMANA, 2013)
The purpose of this research is to: analyze financial performance Tegal local government in terms of the ratio of the area of financial independence, analyzing financial performance Tegal local government spending efficiency in terms of ratios, and analyze the financial performance of local governments in terms of Tegal, Tegal PAD effectiveness ratio. The method used in this study is that research using secondary data archival research (archival research) where the data describing past events (historical). Because this study used secondary data from the data collection techniques used is to use a search technique records or documents. Analysis of Variance calculation results Expenditure 2006 to 2010 showed a positive figure, the difference / variance approach the same from year to year . This means that local governments have taken advantage of Tegal is well on budget expenditures that have been made by the Government of Tegal is smaller than the planned budget. Analysis of the calculation results Spending Growth 2006 to 2010 was positive, although when viewed from up and down and the percentage experiencing considerable growth decline in 2010. In general, the City Government has effort Tegal Expenditure utilization in the budget is always positive growth. Efficiency Analysis of the results of calculations Expenditure Tegal from 2006 to 2010 is less than 100 per cent where the smaller the ratio, the more efficient spending, and vice versa. Budgets will be efficient if the ratio is less than 100 and vice versa. Keywords: Variance Results Expenditure, Spending Growth, Effectiveness Financing.